Workplace Transformation in the post-Covid-19 World : Deloitte Case Study - Montanaro, Magdalena Zdenka; Orel, Marko, 1986-; Lukeš Rybanská, Ivana, 1991-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The thesis investigates the employee experiences of Deloitte’s Prague office to expand the theoretical comprehension of workplace transformation and hybrid work models. Employee interviews are supported by autoethnographic observations to uncover experiences related to well-being, collaboration, task completion, and employee growth. Four key results emerge from the analysis: 1) underutilization of amenities and spaces intended for the improvement of well-being in the office 2) the importance of real-time communication 3) strategies to balance needs 4) the importance of the office in the development of well-rounded growth. The thesis concludes that employees perceive the office space as an opportunity for collaboration and soft skill development while preferring remote settings for work requiring deep focus. Employees also tend to take care of their well-being outside of the office. The conclusions offer insights for companies seeking to implement similar frameworks.
Vedoucí práce: Marko Orel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses